2020
DOI: 10.3390/app10082648
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Activity of Poly- and Oligosaccharides Obtained from Plantago major L. Leaves

Abstract: The aim of the present study was to evaluate the prebiotic potential of Plantago major L. leaves water-extractable polysaccharide (PWPs) and its lower molecular fractions. The structure of PWPs was investigated by high pressure anion exchange chromatography (HPAEC), size exclusion chromatography coupled with multi-angle laser light scattering detector (SEC-MALLS) and Fourier-transform infrared (FTIR) spectroscopy. The chemical composition and monosaccharide analyses showed that galacturonic acid was the main m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…Indeed, it is well known that the pH decrease could be explained by the fact that S. thermophilus produces little amounts of formic acid and CO2 59 . The obtained results in this research agree well with those reported by Seleet et al 60 Benahmed-Djilali et al 5 , and Lukova et al 16 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, it is well known that the pH decrease could be explained by the fact that S. thermophilus produces little amounts of formic acid and CO2 59 . The obtained results in this research agree well with those reported by Seleet et al 60 Benahmed-Djilali et al 5 , and Lukova et al 16 .…”
Section: Discussionsupporting
confidence: 93%
“…Recently, the pectin type water extractable polysaccharides from Plantago major L. gained greater attention as a prebiotic that stimulates the growth of some Lactobacillus strains 16 . The analysis of phytochemicals and nutraceuticals of the vine leaf extract reveals the presence of phenolic compounds and polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…However, this search did not identify a study where these species had been tested against specific gynecological pathogens or the vaginal microbiota. There were studies indicating that plants, such as Aloe vera, Plantago major L., and Opuntia ficus-indica (L.) Mill., have prebiotic activity for gut Lactobacilli (Guevara-Arauza et al 2012;Lukova et al 2018;Paz Quezada et al 2017). This may also be relevant to the treatment of gynecological infections.…”
Section: Resultsmentioning
confidence: 99%
“… Seed husks Alkaline (0.5 M NaOH) 61.4% Xyl (71.16%), Ara (24.52%), Man (1.74%), Gal (1.82%), Rha (0.76%), ( Guo et al, 2008 ) P. ovata Forssk. Seed husks Alkaline (2 M NaOH) 45% 3.64 × 10 5 Xyl (74.8%), Ara (23.2%), Gal (1.2%), Rha (0.8%) ( Saghir et al, 2008 ) P. asiatica L. Leaves Hot water 3.54 × 10 4 GalA (36.5%), Gal (34.4%), Ara (10.1%), Rha (8.4%) ( Yin et al, 2019 ) P. lanceolata L. Leaves Hot water (80℃) 0.64% GalA (70.58%), Ara (29.42%) ( Lukova, Karcheva-bahchevanska, Nikolova, & Mladenov, 2017 ) P. major L Leaves Hot water (80℃) 1.92% 6.60 × 10 4 GalA (55.38%), Glu (21.50%), Ara (9.88%), Gal (8.02%), Rha (3.17%), Xyl (2.05%) ( Lukova et al, 2020 ) P. media L. Leaves Hot water (80℃) 2.79% GalA (64.88%), Ara (35.12%) ( Lukova et al, 2017 ) P. notata Lag. Leaves Hot water (70℃) 2.0% Gal (43.95%), Rha (20.28%), GalA (12.57%), Glu (11.30%), Ara (9.55%) ( Boual, Chouana, Kemassi, Hamid Oudjana, Daddi Bouhoun, Michaud, et al, 2015 ) P. ovata Forssk.…”
Section: Extraction Physicochemical Properties and Structural Featuresmentioning
confidence: 99%
“…It is well recognized that the Plantago polysaccharides are difficult or slow to be fermented, either in vivo or in vitro ( Gunn et al, 2020 , Marteau et al, 1994 ), which has been considered as a typical low-fermenting fiber ( Gill et al, 2020 , O’Grady et al, 2019 ). When treated by microwave, ultrasound, ball milling, or enzymatic hydrolysis, the molecular weight and viscosity of those polysaccharides often decrease, and it is easier to be fermented by the flora and produce more SCFAs, reflecting better prebiotic activity ( Hu et al, 2013 , Hu et al, 2018 , Lukova et al, 2020 , Pollet et al, 2012 ). Therefore, how to improve the fermentation of Plantago polysaccharides to improve their prebiotic activity is one of the hot research fields currently.…”
Section: Prebiotic Activity Of Plantago Polysaccharidesmentioning
confidence: 99%